1973
DOI: 10.1136/oem.30.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Role of dust in the working environment in development of chronic bronchitis in British coal miners

Abstract: , 217-226. Role of dust in the working environment in development of chronic bronchitis in British coal miners. In the course of a long-term prospective study of chronic respiratory disase in British coal miners the effects on pulmonary ventilatory function of exposure to airborne dust, of simple pneumoconiosis, and of chronic bronchitis have been examined in a group of 3581 coalface workers.The men were employed in 20 collieries throughout the British coalfields. Their cumulative exposures to coal mine dust i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 12 publications
7
47
0
3
Order By: Relevance
“…Much debate centred on whether this excess of respiratory disease was related to occupation or to other social differences. Subsequently the likelihood of having persistent productive cough,78 of having a low FEVY, 9 -12 and of suffering excessive loss of FEV, over a period'3 was shown to be influenced by a man's cumulative lifetime exposure to respirable dust, confirming that occupational exposure contributed to the excess of respiratory disease in coalminers.…”
mentioning
confidence: 69%
“…Much debate centred on whether this excess of respiratory disease was related to occupation or to other social differences. Subsequently the likelihood of having persistent productive cough,78 of having a low FEVY, 9 -12 and of suffering excessive loss of FEV, over a period'3 was shown to be influenced by a man's cumulative lifetime exposure to respirable dust, confirming that occupational exposure contributed to the excess of respiratory disease in coalminers.…”
mentioning
confidence: 69%
“…Many reports define PSDs ranging from 0Á7 to 5 lm for lyophilized spores to which silica was added as a fluidizing agent (Buttner et al 2001;Brown et al 2007;Baron et al 2008). Based on these data, our experience and that the respirable range is 1-5 lm (Rogan et al 1973), the DQO for count median diameter (CMD) of the PSD was justifiably defined as 2Á0 AE 1Á0 lm. Of numerous studies aerosolizing spores, only four reported using lyophilized spore powders.…”
Section: Introductionmentioning
confidence: 99%
“…(4)(5)(6) Outros estudos (7)(8) destacaram a importância da associação entre a limitação crônica ao fluxo aéreo e a exposição prolongada a poeiras minerais. Em análise sobre estudos epidemiológicos de base populacional, de avaliação longitudinal da função pulmonar, de histopatologia com interesse na quantificação do enfisema e em estudos de mortalidade, procurou-se destacar a evidente relação causal entre a DPOC e as atividades, independentemente do tabagismo.…”
Section: Introductionunclassified